Estimation of total in skewed population - Krapavickaitė, Danutė; Turkuvienė, Jurgita (Lietuvos matematikos rinkinys, 2001)
Aim of this paper is to estimate total of the crop of winter wheat in the skewed population of farmers in Lithuania using different sampling strategies, to compare the estimates with the true value, to compare the methods with each other and to find out the most suitable strategy for the estimation of the total.